Borehole deformation under a stressed state and in situ stress measurement - Wang, C.Y.; Han, Z.Q.; Wang, Y.T.; Wang, J.C. (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
In engineering practice, in situ stress measurement is usually done using methods such as hydraulic fracturing and stress relief. Despite their advantages, these methods also have shortcomings including difficulty in determining stress directions, complexity of testing process, and limits in applicable borehole depth. In this study, we set out to investigate borehole morphology under stress based on theories of elastic mechanics, and propose an in situ stress measurement approach based on borehole deformation. We theoretically prove a circular hole plane under stress will be elliptical in shape, and derive the equations depicting the relationship between the elliptical parameters and the stresses. We developed a probe microscopy-based borehole measurement method, and performed laboratory simulation and system calibration tests to verify its viability and accuracy. This approach may serve as a new method for in situ stress measurement.